P-089 SPONTAONEUS BOWEL EVISCERATION IN UMBILICAL HERNIA: CASE REPORT. (13th October 2022) - Grappolini, N; Garbarino, S; Fanelli, M; Scorza, A; Marzorati, A; Colombo, E M; Palillo, A; Palamara, N; Inversini, D; Ietto, G; Carcano, G
Abstract: Aim: Spontaneous rupture of sac of hernia is a less common complication and mainly associated to persistent ascites or congenital wall defects. In literature we have few cases of spontaneous bowel eviscerations in umbilical hernias. Case Report: a 53-year-old male years old man addicted to heroin, cocaine and alcohol, presented to the Emergency Department with evisceration of small bowel through an existing umbilical hernia. The patient was conscious and not complaining pain. He stated a protrusion of small bowel through his umbilical skin caused to sudden coughing after assumption of a dose of heroin.In emergency room showed an ileal loop with sub ischemic features. Blood test revealed an hepatitis C infection. During the urgent laparotomy there wasn't evidence of ascites and was necessary to performed an ileal resection and latero-lateral anastomosis with mechanical suturing machine. The placement of a prosthesis was performed; therefore, direct plastic surgery of the abdominal wall. After surgery with a short stay in ICU of 24 hours, the patient was discharged in POD 5. The postoperative course was regular without wound complications. After four months he was free from recurrence and VAS was 0. Conclusions: Spontaneous bowel eviscerations in umbilical hernias is associated with refractory ascites in cirrhotic patients or congenital defect. This case is one of few case depicted in literature as spontaneous evisceration of bowel in non cirrhotic patient with umbilical hernia.